Automation of a temporary immersion technique based on open platforms of hardware and software. - Lugo Espinosa, Oziel; Arellano Ostoa, Gregorio; Hernández Cote, Diego (REVISTA TERRA LATINOAMERICANA, 2017)
A Temporary Immersion System (TIS) enables plant micropropagation in unsterilized sealed environments. However, it is a complicated and expensive technology. In this paper, an automation alternative based on open hardware and software platforms is presented, with the objectives of reducing costs and increasing performance as compared with commercial systems, through software reconfiguration of routines for nutrient application, constant monitoring and remote control of the system. For hardware development, the Bottom Up methodology was used, and Kanban methodology was used for the software. The cost of the proposed system is on average 10% that of commercial electronic devices used in the industry to solve process automation problems. Growth assessment of the explants is necessary to corroborate the competitive advantages of the prototype relative to the traditional systems of temporary immersion.